A new definition for global bioethics: COVID-19, a case study. Issue 1 (31st December 2022) - Macklin, Ruth
ABSTRACT: A truly global bioethics involves cooperation and collaboration among countries. Most of the articles published in bioethics journals address a problem that exists in one or more countries, but the articles typically do not discuss solutions that require collaboration or cooperation. COVAX is one example of proposed international cooperation related to the current COVID-19. pandemic. Yet it is evident that nations have been proceeding on their own with little, if any collaboration. Despite international research ethics guidance from the World Health Organization (WHO), an article published under WHO auspices violates an ethical principle rejecting "double standards" in the conduct of global research. The COVID pandemic provides an opportunity for countries to learn from the recent lack of international cooperation and employ a multi-national strategy in future global health crises.